Layanan Pendidikan Bagi Anak Pekerja Migran di Sanggar Bimbingan Belajar Kuala Lumpur, Malaysia - Anastasya Rahma Nur Faizah; Arif Mansyuri; Hanun Asrohah; Muhammad Nuril Huda; Ebta Sitanggang; Mashudi Mashudi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the educational services provided at the Kuala Lumpur Learning Centre, the role of the Indonesian School in Kuala Lumpur (SIKL) in supporting the delivery of education, as well as the enabling and hindering factors encountered in its implementation. This study employs a descriptive qualitative approach. Data was collected through interviews, observations, and documentation involving representatives from SIKL, the centre’s coordinator, and teaching staff The results of the community service project indicate that the Kuala Lumpur Learning Centre serves as an alternative educational service for children of Indonesian migrant workers who are unable to access formal education. SIKL plays a role in supporting the sustainability of educational services through teacher training, academic support, learning monitoring and coordination with various parties. Supporting factors include support from the Indonesian Embassy in Kuala Lumpur, Indonesian community organisations, educational volunteers, and community participation. Meanwhile, inhibiting factors include limited infrastructure, a shortage of teaching staff, and administrative constraints for students.